Resistencia a betalactámicos de agentes bacteriémicos - Zambrano Quispe, Osler Nicanor (2017)
Objective: Determine the resistance to beta - lactam antibiotics in bacteremic agents at Hospital Belen De Trujillo, 2006 - 2016. Material and method: We carried out a descriptive, retrospective and cross-sectional study that included 1456 patients with blood-culture confirmed bacteremia, respecting the inclusion and exclusion criteria. The data obtained were from the clinical histories of the Hospital Belen de Trujillo, over 10 years. The results are presenting in tables of double entry and graphs. Results and conclusions: Of the isolated bacteriemic agents, 64.42% were Gram-positive germs and 35.58% Gram-negative germs. Among Gram-positive germs, coagulase negative Staphylococcus 43.13%, S. aureus 29.73% and S. pneumoniae 2.54% were the most frequent. In addition, among Gram-negative germs, E. coli 8.51%, K. pneumoniae 7% and P. aeruginosa 5.21%, were the most frequent. Gram-positive germs had greater resistance to Oxacilin with 74.94%. Gram-negative bacteria had greater resistance to Ampicillin with 48.06%.